The Synergetic Role of Project Effective Communication and Trust in Project Success - Waqas Amin; Rizwan Khan; Hafiz Fawad Ullah; Naqibullah Shaikhzada; Dr. Bilal Khan (Dialogue Social Science Review (DSSR), 2024)
This study investigates the impact of effective communication and trust on project success within the construction industry of Khyber Pakhtunkhwa. Using a cross-sectional survey research design, data were collected from a sample of 218 respondents involved in construction projects. Regression analysis conducted using SPSS revealed that both effective project communication and trust have significant and positive effects on project success. The results suggest that fostering open communication and building trust among project stakeholders can substantially enhance project outcomes. This study contributes to the literature by providing empirical evidence of the synergistic effects of communication and trust on project success, emphasizing their importance in project management practices within the construction sector. This study offers actionable insights for project managers, highlighting the need to integrate communication and trust-building strategies into project management frameworks for improved outcomes.